A study of the association of childhood asthma with HLA alleles in the population of Siliguri, West Bengal, India. Issue 3 (25th June 2014) - Lama, M.; Chatterjee, M.; Chaudhuri, T. K.
Abstract Asthma is a heterogeneous disease for which a strong genetic basis is firmly established. It is a complex disorder influenced by gene–environment interaction. Human leukocyte antigen (HLA) genes have been shown to be consistently associated with asthma and its related phenotypes in various populations. The aim of this study was to determine the frequency of the selected HLA classes I and II allelic groups in asthmatic and control groups. HLA typing was performed using polymerase chain reaction‐sequence‐specific typing (PCR‐SSP) method. The allele frequency was estimated by direct counting. Frequency of each HLA allelic group was compared between asthmatic group and control group using χ2 test. P‐value was corrected by multiplying with the number of the allelic groups studied. Odds ratio (OR) and its corresponding 95% confidence interval (CI) for each allelic group were calculated using graphpad instat 3.10. The results of this study showed a significantly higher frequency of HLA‐DRB1*03 in asthmatics than in controls (11.43% vs 3.64%, OR = 3.78, 95% CI = 1.61−8.85, P = 0.0025, Pcorr < 0.05). Analysis of HLA alleles in low and high total serum immunoglobulin E (IgE) level in asthmatics revealed no significant association. HLA‐DRB1*03 may be implicated in the susceptibility to asthma in the pediatric population.